2011
DOI: 10.5423/ppj.2011.27.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pathogenesis by Light in Cercospora zeae-maydis: An Updated Perspective

Abstract: The fungal genus Cercospora is one of the most ubiquitous groups of plant pathogenic fungi, and gray leaf spot caused by C. zeae-maydis is one of the most widespread and damaging foliar diseases of maize in the world. While light has been implicated as a critical environmental regulator of pathogenesis in C. zeae-maydis, the relationship between light and the development of disease is not fully understood. Recent discoveries have provided new insights into how light influences pathogenesis and morphogenesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Another maize gene in the GY-s module was an orthologue of the rice and Arabidopsis CHY RING zincfinger domain proteins, the mutants of which show reduced stomatal aperture (Hsu et al, 2014). GLS pathogens enter maize leaves through stomata (Kim et al, 2011), thus this gene may represent another target of the pathogen to facilitate stomatal entry.…”
Section: Discussionmentioning
confidence: 99%
“…Another maize gene in the GY-s module was an orthologue of the rice and Arabidopsis CHY RING zincfinger domain proteins, the mutants of which show reduced stomatal aperture (Hsu et al, 2014). GLS pathogens enter maize leaves through stomata (Kim et al, 2011), thus this gene may represent another target of the pathogen to facilitate stomatal entry.…”
Section: Discussionmentioning
confidence: 99%
“…nidulans , their activity may be repressed in the darkness through the action of other photoreceptors or regulatory proteins in signaling pathways governing the sexual development of F . graminearum [ 11 , 12 , 39 ], or 2) unlike the protein interaction model in A . nidulans where FphA physically interacts with LreB [ 12 ], our results showed that FgFph interacts with FgWc-1 in F .…”
Section: Discussionmentioning
confidence: 99%
“…In some fungal species, light regulates when toxins and other secondary metabolites are produced [30,[33][34][35][36][37][38]. In Cercospora species that produce the light-activated phytotoxin cercosporin, light induces production of the toxin, as that is when it is most effective [39,40], and no cercosporin is produced in the dark.…”
Section: Introductionmentioning
confidence: 99%